Association of lunch meat consumption with nutrient intake, diet quality and health risk factors in U.S. children and adults: NHANES 2007–2010. Issue 1 (December 2015) - Agarwal, Sanjiv; Fulgoni, Victor; Berg, Eric
Abstract Background Consumption of lean meat is recommended as part of healthy diet byDietary Guidelines for Americans, 2010 . Lunch meats are precooked or cured meats typically used in sandwiches and are also called as cold cuts or deli meat. Objective The purpose of the study was to examine the association of lunch meat consumption with nutrient intake, diet quality, and physiological measures in children (age 2–18 years;n  = 5, 099) and adults (age 19 years and older;n  = 10, 216) using a large, nationally representative database. Methods Lunch meat consumers were defined as those consuming any amount of lunch meat during a 24-h recall and association with nutrient intake, diet quality (Healthy Eating Index (HEI)-2010 score) and physiological measures were evaluated using the National Health and Nutrition Examination Survey (NHANES), 2007–2010. Results The lunch meat consumers (both children and adults) had higher intakes of calories, protein, calcium, potassium, sodium and saturated fat (for adults only) compared to non-consumers. Lunch meat intake was also associated with higher intake of meat/poultry/fish food group in both children and adult consumers than non-consumers. There was no difference in total HEI-2010 scores comparing lunch meat consumers and non-consumers in children or adults. However, HEI components scores for total fruit, whole fruit (children only), whole grains, dairy and total protein foods were significantly higher, and for greens & beans (adults only), seafood and plant protein, fatty acid ratio and sodium were significantly lower in children and adult lunch meat consumers compared to non-consumers. There were no significant differences in physiological measures or in the odds ratios of health related conditions between lunch meat consumers and non-consumers in children or adults. Conclusions The results of this study may provide insight into how to better utilize lunch meats in the diets of U.S. children and adults.